Digital Breast Tomosynthesis: Dose and image quality characterization. (September 2016) - Fezzani, K.; Sage, J.; Fitton, I.; Hadid, L.; Moussier, A.; Pierrat, N.; Martineau, A.; Etard, C.
Abstract : Introduction: Digital Breast Tomosynthesis (DBT) offers a gain in sensitivity and in specificity for detection of breast cancers compared to 2D mammography, due to tissues' overlapping reduction. The introduction of this technique within the French breast cancer screening program is being considered by the authorities in the coming years. Purpose: The aim of the study is to compare different DBT systems in term of dose and image quality. The evaluation of different image quality phantoms could lead to recommendations for incoming French regulatory internal quality control. Materials and methods: Five French hospitals with three different tomosynthesis systems and seven specific phantoms have been included in the study. Average Glandular Dose and SDNR are assessed for different thicknesses of PMMA. Regarding image quality, reconstructed images are analyzed on global score, spatial resolution, geometrical distortion and homogeneity aspects. Results: Preliminary results on dose and image quality for different models and modes are expected in May 2016 and will be discussed, as well as image quality and phantoms' sensibility at different dose levels. Conclusion: The diversity in design of Digital Breast Tomosynthesis systems leads to an expected variability in terms of image quality and dose with breast thickness. Particular attention should be paid to the increase of the dose. Work at a national level on the regulatory quality control of tomosynthesis systems should be initiated as soon as possible in France. Disclosure: FITTON I: co-inventor of Tomomam® phantom.